1968
DOI: 10.1042/bj1080797
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of aromatic acids by micro-organisms. Metabolic pathways in the fungi

Abstract: 1. The metabolic pathways of aromatic-ring fission were examined in a range of fungal genera that utilize several compounds related to lignin. 2. Most of the genera, after growth on p-hydroxybenzoate, protocatechuate or compounds that are degraded to the latter (e.g. caffeate, ferulate or vanillate), rapidly oxidized these compounds, but not catechol. 3. Such genera possessed a protocatechuate 3,4-oxygenase and accumulated beta-carboxymuconate as the product of protocatechuate oxidation. This enzyme had a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
92
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(99 citation statements)
references
References 56 publications
7
92
0
Order By: Relevance
“…I) serves in many aerobic bacteria to transform catechol, protocatechuate and their respective precursors to succinate and acetyl-CoA. The regulation of the enzymes operative in this pathway has been extensively investigated in a number of species of Pseudomonas (Ornston, 1966a;Kemp & Hegeman, 1968;Stanier, 1968;RobertGero, Poiret & Stanier, 1969) and in Moraxella calcoacetica (Cgnovas & Stanier, 1967), Alcaligenes eutrophus (Johnson & Stanier, 1971) and several Nocardia species (Rann & A general survey of the routes utilized by fungi for the catabolism of aromatic compounds (Cain, Bilton & Darrah, 1968) confirmed the widespread existence of the 3-oxoadipate pathway within this group. In all the fungal genera examined the subsequent metabolism of the ring cleavage product, 3-carboxymuconate, proceeded through 3-carboxymuconolactone rather than through the 4-substituted isomer characteristic of the bacteria, confirming an earlier observation in Neurospora crassa (Gross, Gafford & Tatum, 1956).…”
Section: Introductionmentioning
confidence: 99%
“…I) serves in many aerobic bacteria to transform catechol, protocatechuate and their respective precursors to succinate and acetyl-CoA. The regulation of the enzymes operative in this pathway has been extensively investigated in a number of species of Pseudomonas (Ornston, 1966a;Kemp & Hegeman, 1968;Stanier, 1968;RobertGero, Poiret & Stanier, 1969) and in Moraxella calcoacetica (Cgnovas & Stanier, 1967), Alcaligenes eutrophus (Johnson & Stanier, 1971) and several Nocardia species (Rann & A general survey of the routes utilized by fungi for the catabolism of aromatic compounds (Cain, Bilton & Darrah, 1968) confirmed the widespread existence of the 3-oxoadipate pathway within this group. In all the fungal genera examined the subsequent metabolism of the ring cleavage product, 3-carboxymuconate, proceeded through 3-carboxymuconolactone rather than through the 4-substituted isomer characteristic of the bacteria, confirming an earlier observation in Neurospora crassa (Gross, Gafford & Tatum, 1956).…”
Section: Introductionmentioning
confidence: 99%
“…HARRIS and RICKETTS (10 ) and CAIN et al ( 4 ) reported that the utilization of phenol for growth by some yeast strains occurred only after the cultivation of 1 to 2 weeks. In the present experiment, the growth of C. tropicalis on phenol was excellent compared with the growth on other carbon sources including catechol and methylcatechols, and reached a maximum value after 2 days' incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, FEIST and HEGEMAN (3) showed that the bacteria grown on phenol contained an enzyme which catalyzed the benzene ring cleavage by an extra-diol type fission, and that the bacteria grown on benzoate contained an enzyme which catalyzed the cleavage by an intra-diol type fission. CAIN et al (4) studied the oxidation of phenols that were related to lignin by various strains of fungi and yeasts using whole cells and cell-free extracts.…”
mentioning
confidence: 99%
“…The biochemistry of the pathway is similar in both groups of micro-organisms, although in all fungi the subsequent metabolism of the ring cleavage product, 3-carboxymuconate, proceeds through 3-carboxymuconolactone (Gross, Gafford & Tatum, 1956;Cain, Bilton & Darrah, 1968~) rather than through the 4-substituted isomer as in bacteria (Stanier & Ornston, 1973).…”
Section: Introductionmentioning
confidence: 99%